Apolipoprotein L1 and Kidney Disease in African Americans. (April 2016) - Friedman, David J.; Pollak, Martin R.
Abstract : Genetic variants in the Apolipoprotein L1 (APOL1) gene cause high rates of kidney disease in African Americans. These variants, found only in individuals with recent African ancestry, confer enhanced innate immunity against African trypanosomes. Although they are among the most powerful disease-causing common variants discovered to date, we are just beginning to understand how they promote kidney injury. Since APOL1 is present in only a few primate species, much of our current knowledge has come from natural experiments in humans and in vitro studies while awaiting the development of transgenic animal models. Understanding more about the function of ApoL1 and how the high-risk variants behave differently from other ApoL1 molecules is a high priority in kidney disease research. Trends: Genetic variants in the apolipoprotein L1 (APOL1) gene account for a large fraction of the high rates of nondiabetic kidney disease in African Americans. APOL1 risk variants have large effects on several different types of kidney disease previously thought to be distinct entities. The high-risk APOL1 variants are unusually common for such deleterious genetic variants, probably because they conferred a survival advantage in sub-Saharan Africa by enhancing innate immunity against trypanosomes and possibly other pathogens. Despite the recessive mode of inheritance, evidence suggests that the APOL1 high-risk variants are likely to be toxic gain-of-function mutations. APOL1 possess two domains that may contribute to kidney cell death: a colicin-like domain that acts as an ion channel and a BH3-only death domain that may influence autophagy or apoptosis.